2022
DOI: 10.1016/j.gocm.2022.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body mass index, anti-müllerian hormone and insulin resistance parameters among different phenotypes of polycystic ovary syndrome

Abstract: BackgroundDiagnosis of polycystic ovary syndrome (PCOS) depends on 2003 Rotterdam Criteria. According to these criteria there are four possible combinations resulting in various phenotypes. We aimed (i)to confirm that the levels of body mass index (BMI), anti-müllerian hormone (AMH) levels and insulin resistance (IR) are higher in PCOS patients and higher in phenotype-A among PCOS patients, and (ii)to determine cut-off values for the diagnosis of PCOS and phenotype-A.Materials and methodsThis study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Interestingly, within the scope of the current investigation, distinct classifications displayed varying degrees of performance in effectively discerning the biomarkers associated with HA. Soyman et al reported the highest level of free testosterone in phenotype A and the lowest level in phenotype D [33,34], whereas Gursu et al found that DHEAS levels were highest in phenotype A and the lowest in phenotype B [35]. Given the limitations of measuring TT and direct free testosterone in females [4,36,37], FAI was also employed in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, within the scope of the current investigation, distinct classifications displayed varying degrees of performance in effectively discerning the biomarkers associated with HA. Soyman et al reported the highest level of free testosterone in phenotype A and the lowest level in phenotype D [33,34], whereas Gursu et al found that DHEAS levels were highest in phenotype A and the lowest in phenotype B [35]. Given the limitations of measuring TT and direct free testosterone in females [4,36,37], FAI was also employed in the present study.…”
Section: Discussionmentioning
confidence: 95%